Performing politics at the Israeli security fair - Grassiani, Erella (Policing and society, 2024)
Fairs, markets and bazaars are primarily commercial activities. Historically, however, through the accumulation of wealth they enable and due to their often strategic locations, they have also been sites at which political alliances are made and empires founded. Surprisingly, most debates on the politics of markets are consumer-oriented and rarely focus on their geopolitical importance. In this article, I analyse the Israeli security fair as a political event. Israel’s security industry is booming; its global export is worth billions, and it attracts thousands of potential international clients. To show how politics are conducted and constructed at the security fair, I will look beyond the neoliberal idea that gives ‘the market’ powers of its own and implies that market forces are neutral and non-political. By expanding the operationalisation of politics to include discursive, visual and material performances, I will not only argue that the fair is inherently political but also present a novel way in which to see such politics. Importantly, while exploring politics through the ways in which they are performed, I will emphasise the embeddedness of the fair and its politics in orientalist and colonialist logics.